SCAT uncovers ATLAS's first tidal disruption event ATLAS18mlw: a faint and fast TDE in a quiescent Balmer strong Galaxy. Issue 2 (19th December 2022) - Hinkle, Jason T; Tucker, Michael A; Shappee, Benjamin J; Holoien, Thomas W-S; Vallely, Patrick J; de Jaeger, Thomas; Auchettl, Katie; Aldering, Greg; Ashall, Chris; Desai, Dhvanil D; Do, Aaron; Payne, Anna V; et al.
ABSTRACT: We present the discovery that ATLAS18mlw was a tidal disruption event (TDE) in the galaxy WISEA J073544.83+663717.3, at a luminosity distance of 334 Mpc. Initially discovered by the Asteroid Terrestrial Impact Last Alert System (ATLAS) on 2018 March 17.3, the TDE nature of the transient was uncovered only recently with the re-reduction of a SuperNova Integral Field Spectrograph (SNIFS) spectrum. This spectrum, taken by the Spectral Classification of Astronomical Transients (SCAT) survey, shows a strong blue continuum and a broad H α emission line. Here, we present roughly 6 yr of optical survey photometry beginning before the TDE to constrain active galactic nucleus activity, optical spectroscopy of the transient, and a detailed study of the host galaxy properties through analysis of archival photometry and a host spectrum. ATLAS18mlw was detected in ground-based light curves for roughly 2 months. From a blackbody fit to the transient spectrum and bolometric correction of the optical light curve, we conclude that ATLAS18mlw is best explained by a low-luminosity TDE with a peak luminosity of log(L [erg s −1 ]) = 43.5 ± 0.2. The TDE classification is further supported by the quiescent Balmer strong nature of the host galaxy. We also calculated the TDE decline rate from the bolometric light curve and find Δ L 40 = −0.7 ± 0.2 dex, making ATLAS18mlw a member of the growing class of 'faint and fast' TDEs with low peak luminosities and fast decline rates.